RELATIONSHIP BETWEEN TEMPERATURE OF DRYER CHAMBER AND RATE OF FUEL SUPPLIES FROM THREE KINDS OF BIOMASS FUEL - Meidi Satriawan Sipayung; Yuwana Yuwana; Bosman Sidebang (Jurnal Agroindustri, 2015)
The purpose of this study was to determine the number of supply of (initial and subsequent) fuel to achieve the target temperature and determine the rate of fuel supply relationship with temperature drying chamber. Biomass was used are palm shells, pecan shells and coconut shells. Results of research showed that fuel supply rate (Q / 40 min) to produce a temperature (T), which is different from the fuel pecan shells, palm shell and coconut shell follows the following equation: initial supply hazelnut shells obtained from the equation T = 13,9Q + 19.3 with R² = 0.983 and the subsequent supply is obtained by the equation T = 12,24Q + 39 with R² = 0.971, the initial supply of palm shells obtained from the equation T = 8,925Q + 29.55 with R² = 0.964 and the subsequent supply is obtained by the equation T = 15 , 27Q + 29.09 with R² = 0.989, the initial supply of coconut shell derived from the equation T = 19,8Q + 0.6 with R² = 0.972 and the subsequent supply is obtained by the equation T = 19,37Q + 34.86 with R² = 0.994 .